Ephemeral vistas the expositions universelles, great exhibitions and world's fairs, 1851-1939 - Greenhalgh, Paul 1955- ([Manchester University Press], 2017)
The Great Exhibition of 1850 transformed everyone's vision of what an exhibition might be. The first truly international event of its kind, it was an encyclopaedic attempt to sum up the progress of the world so far. But it was not simply a cultural manifestation aiming to educate and enlighten: it also had very particular social and political motives. At the core of the Exhibition was the imperial idea, that Europe in general and Britain in particular led and controlled the world. After 1851, other Western nations staged their own exhibitions, these frequently being larger and more flamboyant than the British prototype. Amongst these, the Expositions Universelles held in France and the World's Fairs held in America were the most impressive. Into the twentieth century the scale and opulence of the exhibitions reached a pitch which now defies imagination. Socio-political motives often dominated, the objects on display conveying a plethora of coded messages to their massive audiences. 'Ephemeral Vistas' attempts to understand these messages, returning the exhibitions as far as possible to their original historical contexts. Many exhibitions which have fallen into obscurity are reassessed, and new material on well known events is presented. Much of this is of interest not only to art and design historians, but also to anthropologists, sociologists, social and political historians, and all those interested in popular culture. In a wider sense, the book is of general interest for the way it reveals exhibitions as creators of lasting monuments. Cities were transformed to accommodate exhibitions, and in many instances features remain to mark the places where these extraordinary events took place
Auf der Landingpage (Manchester Hive): "Online Publication Date: 01 Mar 2017"
Keywords: Geschichte 1851-1939; Colonialism & Imperialism / bicssc; HISTORY / Europe / Great Britain / bisach; History / thema; Trade shows / History; Exhibitions / History; Ausstellung; International exhibitions / 1851-1939